Multisectoral Integration of Nutrition, Health, and Agriculture: Implementation Lessons From Ethiopia. Issue 2 (June 2020) - Bach, Ashley; Gregor, Erin; Sridhar, Shela; Fekadu, Habtamu; Fawzi, Wafaie
Background: The Government of Ethiopia and development partners have invested heavily in nutrition through multisectoral nutrition programs and the recently announced Food and Nutrition Policy. By making nutrition a political priority, the government has enabled multisectoral collaboration. Objective: To trace the development of multisectoral nutrition policy in Ethiopia and identify lessons learned from implementation. Methods: We utilize the literature and stakeholder interviews across government ministries, donors, and nongovernmental organizations (NGOs) to analyze Ethiopia's progress toward multisectoral nutrition governance through 5 lenses: coordination and structural accountability, political commitment, financing, human resources, and data monitoring and transparency. Results: Despite significant progress, coordination and structural accountability for nutrition activities and outcomes across and within sectors remain challenges. While political will is strong, financing is often insufficient. Ethiopia has a shortage of nutrition policy makers and experts but is investing in education to close this gap. Finally, wider sharing of data across ministries and partners would enable enhanced feedback and improvement upon existing programs. Several lessons are notable for policy makers and partners: (1) making nutrition a national political priority is key to fostering multisectoral collaboration and improving nutrition outcomes; (2) nutrition champions are critical for political prioritization of nutrition; (3) multisectoral collaboration has helped reduce undernutrition in Ethiopia, due to expansion from nutrition-specific to nutrition-sensitive strategies; and (4) accountability structures are vital to effective coordination, monitoring, and evaluation in multisectoral nutrition governance. Conclusions: Ethiopia has made significant progress toward multisectoral integration for nutrition. Despite contextual differences, lessons learned from Ethiopia may guide other countries aiming to reduce malnutrition.